デキストラン硫酸ナトリウムを用いた軽度炎症性腸疾患モデルマウスの開発とコリンエステラーゼ阻害薬による抗炎症作用 - 植松, 若那; 堀江, 俊治; 森, 安大; 田嶋, 公人 (日本薬理学会年会要旨集, 2019)
Low-grade inflammation persists in many patients with clinically quiescent inflammatory bowel disease　(IBD). The current study aimed to establish low-grade IBD model mice. In addition, the anti-inflammatory　effect of the cholinesterase inhibitor neostigmine was also investigated in this model. C57BL/6J mice were used. Colitis was induced by the addition of 0.1–3%(w/v) dextran sulfate sodium (DSS) to drinking water for 7 days. Following 3% DSS treatment, weight loss, appearance of bloody stool and changes in stool quality were evident by day 4 and peaked at day 7. DSS at 1% elicited low-grade inflammation in the colonic　mucosa and increased myeloperoxidase (MPO) activity. In immunohistochemical study, increased MPO-immunopositive neutrophils were observed in the colonic mucosa of low-grade colitis model. Neostigmine dose-dependently inhibited the increase of MPO activity. The α7-nicotinic receptor antagonist partly　reversed anti-inflammatory effect of neostigmine. In conclusion, we suggest that low-grade IBD model mice are established by using 1% DSS-containing drinking water, and neostigmine provides anti-inflammatory　effect through the stimulation of α7-nicotinic receptors in this model.